Prevalence, Associated Factors, and Health Expenditures of Noncommunicable Disease Multimorbidity—Findings From Gorakhpur Health and Demographic Surveillance System - Reddy, Mahendra M.; Zaman, Kamran; Yadav, Rajaram; Yadav, Priyanka; Kumar, Kaushik; Kant, Rajni (Frontiers in Public Health, 2022)
Background: Noncommunicable disease (NCD) multimorbidity throws a unique challenge to healthcare systems globally in terms of not only management of disease but also familial, social and economic implications associated with it. Objectives: To assess the prevalence of NCD multimorbidity and its associated risk factors among adults (≥18 years) living in a rural area. Methods: A secondary data analysis of the first-round survey done as part of the Gorakhpur Health and Demographic Surveillance Site (GHDSS) was done. Information related to self-reported morbidity and other variables related to socio-demographics and out-of-pocket expenditure (OOPE) was captured using a pre-tested questionnaire. Multivariable cluster adjusted binomial regression analysis was done to identify factors associated with multimorbidity. Results: The overall prevalence of NCD multimorbidity was found to be 1.8% (95% CI: 1.7% - 1.9%). The prevalence of NCD multimorbidity was highest among elderly (≥60 years) [6.0% (95% CI: 5.5% - 6.5%)] and among females [2.4% (95% CI: 2.3% - 2.6%)]. Socio-demographic factors like age, gender, occupation, education, marital status, religion, caste and household wealth were all found to be independently associated with NCD multimorbidity. The median annual OOPE was found to be significantly higher among those with NCD multimorbidity (₹20000) compared to those with no NCD (₹5000) or having only one NCD (₹8000). Conclusions: Among the adults in GHDSS, about 13 in every 100 were suffering from at least one NCD and around two in 100 were having NCD multimorbidity. Those with NCD multimorbidity spent almost four times higher annual OOPE compared to those without NCDs.